A taxonomic review of the wolf spider genus Agalenocosa Mello-Leitão (Araneae, Lycosidae) - Piacentini, Luis Norberto (2014)
The lycosid genus Agalenocosa Mello-Leitão, 1944 comprises at least eight species from northern and eastern Argentina and neighbouring countries: Agalenocosa velox (Keyserling, 1891) comb. nov. (from southern Brazil and Argentina), transferred here from Pirata Sundevall, 1833, A. tricuspidata (Tullgren, 1905) comb. nov. (from northwestern Argentina), transferred here from Pardosa C.L. Koch, 1847, A. luteonigra (Mello-Leitão, 1945) (from Argentina and Uruguay), A. punctata Mello-Leitão, 1944 (from Buenos Aires and Entre Ríos, Argentina), A. gentilis Mello-Leitão, 1944 (from Buenos Aires, Argentina), and three new species: A. pirity sp. nov., A. gamas sp. nov. (from eastern Argentina), and A. grismadoi sp. nov. (from eastern Argentina and Paraguay). Agalenocosa singularis Mello-Leitão (type species of the genus) is considered a junior synonym of A. velox. Agalenocosa fimbriata Mello-Leitão, 1944 is considered species inquirenda; Agalenocosa bryantae (Roewer, 1951), A. chacoensis (Mello-Leitão, 1942), A. denisi (Caporiacco, 1947), A. kolbei (Dahl, 1908), A. melanotaenia (Mello-Leitão, 1941), A. pickeli (Mello-Leitão, 1937), A. yaucensis (Petrunkevitch, 1929), A. fallax (L. Koch, 1877), A. helvola (C. L. Koch, 1847), A. subinermis (Simon, 1897) are considered misplaced species. The subfamily placement of Agalenocosa is briefly discussed, and it could be placed in either Piratinae Zyuzin, 1993 or Venoniinae Lehtinen & Hippa, 1979.